A Stochastic Counting MEMS Sensor Using White Noise Oscillation for a High‐Temperature Environment. Issue 9 (6th August 2013) - Hatakeyama, Yohei; Esashi, Masayoshi; Tanaka, Shuji
SUMMARY This paper describes a stochastic counting MEMS sensor that can be used in low‐S/N environments such as high‐temperature plants. A mass that vibrates between two counterelectrodes due to white voltage noise is "pulled‐in" to either of the electrodes by the application of a pulse voltage to the mass. The direction of pull‐in is stochastic, and the probability that the mass is pulled‐in to a particular side depends on mechanical strain applied to the sensor structure. This sensing principle was confirmed by simulation, and the sensor was prototyped using an SOI wafer. Based on our experiment, the probability of pull‐in to a particular side was tuned using a bias voltage applied to the counterelectrodes, as predicted by simulation. When the frequency of the pulse voltage for pull‐in increases, the behavior of the sensor looks random as it is not intended, because the mass is pulled‐in during damping vibration after being released from the previous pull‐in. This limits the sensing speed, but strain sensing is possible by just counting the number of pull‐ins to a particular side, which is easy even in low‐S/N environments. © 2013 Wiley Periodicals, Inc. Electron Comm Jpn, 96(9): 62–70, 2013; Published online in Wiley Online Library (wileyonlinelibrary.com). DOI 10.1002/ecj.10400